Thematic Analysis of the ‘Games' Students Play in Asynchronous Learning Environments - Thalia MacMillan; Michele Forte; Cynthia Grant (Online Learning, 2014)
The dynamics of the student-student relationship within the asynchronous online classroom, as evidenced by conversations in an online discussion board, is one of a balancing act and are potentially more complex than those occurring in real-time. In order for learning to truly be considered effective, a collaborative, safe environment needs to exist among students within the online conversation (McDonald & Gibson, 1998). Conversations and postings made by students were examined by three raters using qualitative analysis. Thematic coding and member checking was conducted. Several prevalent themes emerged around the metaphor of playing a game. Students established rules for the game of asynchronous learning. They followed suit of the lead of player and formed team alliances while establishing who was ‘in’ and who was ‘out’ of the game. Based on these results, strategies have been identified to demonstrate techniques in how instructors can create a more effective learning environment for students, and what strategies can be used to examine and advance conversations, regardless of discipline. The techniques focus on creating awareness among students of potential issues of conflict in asynchronous student to student interactions, how to examine and engage a diversity of student perspectives, and ways to facilitate intellectual growth and advancement in the asynchronous online classroom.